7th IEEE International Conference on Group IV Photonics 2010
DOI: 10.1109/group4.2010.5643389
|View full text |Cite
|
Sign up to set email alerts
|

Detection of lead contamination of water and VOC contamination of air using SOI micro-optical devices

Abstract: Micro-photonic SOI Mach-Zehnder interferometers were coated with solid-phase micro-extraction materials derived from polydimethylsiloxane to enable sensing of volatile organic compounds of the BTEX class in air. A different coating based on functionalized mesoporous silicates is used to detect lead Pb(II) with a detection limit of < 100 ppb in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Full recovery of the material can only be achieved with acidic reconditioning. In our previous experiments, we found that 100 ppb Pb(II) solutions lead to a detectable phase shift that could be recovered with 0.1 M HCl (not shown) [5]. Additional experiments will be performed to determine the true detection limits of lead and mercury using these films.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Full recovery of the material can only be achieved with acidic reconditioning. In our previous experiments, we found that 100 ppb Pb(II) solutions lead to a detectable phase shift that could be recovered with 0.1 M HCl (not shown) [5]. Additional experiments will be performed to determine the true detection limits of lead and mercury using these films.…”
Section: Resultsmentioning
confidence: 88%
“…In our previous work, we coated Mach-Zehnder interferometers with similar functionalized silicate materials [5] but found that the measurement accuracy was limited by the output power variations caused by alignment drifts and laser intensity fluctuations. By using SOI ring resonators, we hoped to obtain resonance wavelength measurements that would not be influenced by light intensity drifts or noise.…”
Section: Resultsmentioning
confidence: 99%
“…Coating them with gas absorbing polymers allowed the detection of xylenes vapor by SPME with a detection limit below 120 ppm. The devices therefore have potential to outperform sensors based on LPFBG [3] and SOI interferometers [4], in addition to simplifying the packaging and the polymer coating process. Future work will involve testing of other siloxane polymers and other gases over a wider range of concentrations, in order to determine more precisely the detection limit and to evaluate the detection specificity.…”
Section: Discussionmentioning
confidence: 99%
“…This was previously demonstrated with long-period fiber Bragg gratings (LPFBG) and with silicon-on-insulator (SOI) Mach-Zehnder RI sensors [3,4]. These sensors are based on the propagation of an evanescent light wave within a thin surface layer at the polymer-sensor interface.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, sensing and reference arms characterized by spiral paths have been proposed in order to concentrate mm -long arms in circular structures with a diameter of the order of few hundreds of micrometers. For example, a sensitivity as high as 4,930 rad/RIU as been experimentally demonstrated for an interferometer realized in SOI technology, with a refractive index change of 8.7 × 10 −7 RIU/ppm of a polydimethylsiloxane (PDMS) layer deposited for sensing of benzene, toluene, ethylbenzene and xylenes [61]. …”
Section: Photonic Sensors For Chemical and Biochemical Detectionmentioning
confidence: 99%